Minnenas magiska lykta: Om Ingmar Bergmans berättelse Laterna magica - Almer, Johan (Scandinavistica Vilnensis, 2023)
Laterna magica (1987) is the first book Ingmar Bergman (1918–2007) published whose content was not intended to be developed into film or theater. This autobiographical book has often been used in research as a reference in various contexts concerning Bergman’s life and art. From a research point of view, however, it is difficult to use the memory book as evidence for facts or truths, as there are many examples of it simply being fiction. It is therefore interesting today to read Laterna magica as a work of art in its own right and thus perhaps find a different “truth” than the one about Ingmar Bergman’s life. For his story of himself, Bergman has very consciously chosen a literary form that structures personal memories interspersed with more contemporary events. What memories then does his literary laterna magica show and what do they mean? Why are memories and events structured in a certain way? Is there any unity in the total of more than a hundred memory images in various forms that the book consists of? My reading of Laterna magica takes a point of departure in Adriana Cavarero’s (2000) theory of the “narrative self.” In Laterna magica the narrative self creates an identity through the story that consists of the merged memory images. It then becomes a story where Bergman’s narrative self is looking for answers to the question “who am I?” The reading of the “autobiography” also assumes that it is a literary work. Thus, the story of the magical lantern of memories can be analyzed as a literary composition where staging and truth-seeking are two important concepts.
Keywords: Ingmar Bergman; Laterna Magica; narrating self; identity; composition; staging; truth-seeking